Incidence and predictive score for delayed hemolytic transfusion reaction in adult patients with sickle cell disease - Narbey, David; Habibi, Anoosha; Chadebech, Philippe; Mekontso‐Dessap, Armand; Khellaf, Mehdi; Lelièvre, Jean‐Daniel; Godeau, Bertrand; Michel, Marc; Galactéros, Frédéric; Djoudi, Rachid; Bartolucci, Pablo; Pirenne, France (American journal of hematology, 2017)
Delayed hemolytic transfusion reaction (DHTR) is a life‐threatening complication of transfusion in sickle cell disease (SCD). The frequency of DHTR is underestimated because its symptoms mimic those of vaso‐occlusive crisis and antibodies (Abs) are often not detectable. No predictive factors for identifying patients likely to develop DHTR have yet been defined. We conducted a prospective single‐center observational study over 30 months in adult sickle cell patients. We included 694 transfusion episodes (TEs) in 311 patients, divided into occasional TEs (OTEs: 360) and chronic transfusion program (CTEs: 334). During follow‐up, 15 cases of DHTR were recorded, exclusively after OTEs. DHTR incidence was 4.2% per OTE (95% CI [2.6; 6.9]) and 6.8% per patient during the 30 months of the study (95% CI [4.2; 11.3]). We studied 11 additional DHTR cases, to construct a predictive score for DHTR. The DHTR mortality is high, 3 (11.5%) of the 26 DHTR patients died. The variables retained in the multivariate model were history of DHTR, number of units previously transfused and immunization status before transfusion. The resulting DHTR‐predictive score had an area under the ROC curve of 0.850 [95% CI: 0.780‐0.930], a negative‐predictive value of 98.4% and a positive‐predictive value of 50%. We report in our study population, for the first time, the incidence of DHTR, and, its occurrence exclusively in occasionally transfused patients. We also describe a simple score for predicting DHTR in patients undergoing occasional transfusion, to facilitate the management of blood transfusion in SCD patients.